2021
DOI: 10.1038/s41598-021-96211-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and microbiology quality of the Pentadesma butyracea fruit pulp collected from various parks in Benin

Abstract: In Benin, P. butyracea fruit pulp undergoes significant post-harvest loss due to its low valorization. The collected fruits in five parklands from a survey of transformer's perception were characterized through their visual observations, the determination of their dimensions and pulp proportions. The nutritional value of pulp was evaluated through its chemical characterization. The results of this study revealed that four shapes (ellipsoid, globular, ovoid, ellipsoid twisted) identify the physical aspect of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The formulation values for Shea pulp (10, 25, and 50%) ranged from 84.39 to 93.01 %. According to reports by Bhalerao et al, (2020), the values obtained were found within the acceptable range for fruit juices (80-95 percent). The study also discovered that Sample C contained the most ash, and the presence of ash has been reported to be an indicator of mineral content (Adedeji et al, 2008).…”
Section: Nutritional Analysismentioning
confidence: 57%
See 1 more Smart Citation
“…The formulation values for Shea pulp (10, 25, and 50%) ranged from 84.39 to 93.01 %. According to reports by Bhalerao et al, (2020), the values obtained were found within the acceptable range for fruit juices (80-95 percent). The study also discovered that Sample C contained the most ash, and the presence of ash has been reported to be an indicator of mineral content (Adedeji et al, 2008).…”
Section: Nutritional Analysismentioning
confidence: 57%
“…After arranging with different dilutions of microorganism suspension, the plates were incubated at 37o C for 48 hours and colonies were counted (Ayegnon et al, 2021).…”
Section: Microbial Analysismentioning
confidence: 99%
“…Forest products contribute to the food security and health promotion of millions of people around the world while providing substantial resources to the national economy (Aissi et al, 2011;Amiri et al, 2021;Avocèvou-Ayisso et al, 2009;Ayegnon et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Forest products contribute to the food security and health promotion of millions of people around the world while providing substantial resources to the national economy (Aissi et al., 2011 ; Amiri et al., 2021 ; Avocèvou‐Ayisso et al., 2009 ; Ayegnon et al., 2021a ). Lately, using quantitative ethnobotanical methods, local communities' knowledge has been investigated to identify promising plants regarding nutritional quality, medicinal properties, and/or commercial potential (Dembélé et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%